Design and analysis of a dual-port multiband RF-to-DC converter for IoT energy harvesting applications - Bismah Tariq; Muhammad Amjad; Khaled A. Al-Jaloud; Waqar Ahmad Malik; Syed Tamoor Shah; Rifaqat Hussain (PLoS ONE, 2025)
Internet of Things (IoT) demands efficient and sustainable energy sources for autonomous power systems. This article presents the design and analysis of a Dual-Port Multiband RF-to-DC Converter employing a multi-stage Cockcroft Walton Voltage Multiplier (CWVM) topology, which is optimized for IoT energy harvesting applications. By utilizing L-network and π-network impedance matching with distributed elements, the converter effectively harvests RF energy across six frequency bands ranging from 0.87 to 2.5 GHz. The dual-port architecture enhances power output and provides redundancy, improving the reliability of the energy harvesting system. While, the multiband feature improves the versatility of energy acquisition. The converter achieves a peak efficiency of 66% and 62% at 10 kΩ and 18 kΩ, respectively. The performance of the proposed design is comprehensively analyzed and optimized, considering the impedance matching, output voltage, and conversion efficiency. The performance of the proposed design is compared with recent converter designs in the literature, which shows that this research is a valuable contribution to the ongoing development of energy-efficient solutions. This work has significant implications for powering low-power sensors, wireless sensor networks, and other IoT devices in diverse environments, addressing the need for prolonged autonomy and reduced reliance on traditional power sources.